Ultra-short laser processing of 3D bioceramic, porous scaffolds designed by freeze foaming method for orthopedic applications - Daskalova, Albena; Ahlhelm, Matthias; Angelova, Liliya; Filipov, Emil; Avdeev, Georgi; Tatchev, Dragomir; Fernandes, Maria-Helena; Vig, Sanjana; Buchvarov, Ivan (Frontiers in Cell and Developmental Biology, 2024)
Bone substitutes are widely employed for applications in orthopedic surgery for the replacement of injured bone. Among the diverse methods that are used to design 3D bioceramic matrices, Freeze Foaming has gained attention, since it provides the ability to tune the shape of the created structures. One of the major problems related to these constructs is the lack of porosity at the outwards sides (holder) of the scaffold, thus reducing the cellular affinity and creating a rejection of the implant. In this research, we aimed to develop a bone scaffold with enhanced surface properties and improved cellular affinity. The main aim was to alter the biocompatibility characteristics of the 3D bioceramic constructs. We have produced three-dimensional, complex-shaped hollow shell structures, manufactured by Additive Manufacturing processes and as a second step, filled with a ceramic suspension by the Freeze-Foaming process. 3D constructs from HAP-derived TCP and TCP/ZrO2 were synthesized by freeze-foaming method and subsequently irradiated with a fs-laser (λ=800 nm) spanning a range of parameters for achievement of optimal surface processing conditions. The designed scaffolds demonstrated enhanced topographical properties with improved porosity examined by SEM, EDX, and 3D profilometry after laser treatment. Wettability and computer tomography (CT) evaluation was also performed. The results from X-ray diffraction (XRD) and micro-Raman analysis did not show photochemical and surface or volume defects and changes after laser processing of the ceramic samples. Preliminary results from MG-63 osteoblast-like cell tests showed good cell affinity on the processed surfaces and no cytotoxic effect on the cells.